Decades of Discord: A Bibliometric Mapping of Agency Problems within Family-Owned Enterprises - Bintang Lazuardi Benteng Buana Muslim; Izlin Ismail (Universitas Proklamasi 45, 2026)
This study aims to identify the intellectual evolution and thematic development of agency problems within family-owned enterprises through a comprehensive bibliometric approach. The bibliometric method was used to analyze publication trends, citations, authorship, and core research themes related to agency conflicts during the period of 2001–2026. Based on the search results, data were collected through the Scopus database using Publish or Perish (PoP), yielding 139 complete articles. The search covered the period from 2001 to 2026, resulting in 139 papers with a total of 432,28 citations per year. Additionally, each paper received an average of 77,75 citations, and the 139 papers collectively had 10,807 citations. Data was retrieved from the Scopus database and processed using Publish or Perish (PoP) and VOSviewer software to map the scholarly landscape. The results show a significant upward trajectory in publications and citations, reflecting a growing global academic interest in the unique governance challenges faced by family firms. Key statistical findings indicate a high citation impact per manuscript, underscoring the foundational nature of this field in corporate finance and management. The thematic analysis grouped the research into four primary clusters: principal-principal conflicts, corporate governance mechanisms, socioemotional wealth (SEW), and firm performance. The findings suggest that while strong family control can minimize traditional manager-owner frictions, it frequently triggers Type II agency costs that jeopardize minority shareholder interests. This study provides critical insights for researchers and practitioners to understand the dynamics of family governance, while highlighting future research opportunities in digital transformation and sustainability to support long-term business resilience.